The Health Promotion Models in Improving the Mental Health of Hemodialysis Patients: A Study on a Holistic Approach - Fahrurozi, M.; Cahyati, Widya Hary; Zainafree, Intan (Journal of Creativity Student, 2025)
Background: mental health is an important component in the treatment of hemodialysis patients, which is often overlooked. Patients face psychological distress due to lifestyle changes, physical limitations, and long-term therapeutic processes that have the potential to trigger depression and anxiety. Aim: This study aims to evaluate the effectiveness of the Health Promotion Model (HPM) approach in improving the mental health of hemodialysis patients through holistic interventions. Method The research used a mixed-methods approach with a pre-test and quasi-experimental post-test with a control group design. Interventions include health education, stress management, psychological counselling, and strengthening social support. The results of the quantitative analysis showed a significant improvement in patients' mental health scores in the intervention group compared to the control group. Qualitative data reveal changes in disease perception, improved adaptive coping strategies, and the important role of social support in maintaining emotional stability. Conclusion: The holistic application of HPM is effective in strengthening psychological resilience and improving the quality of life of hemodialysis patients. This intervention is recommended to be systematically integrated into hemodialysis services in health facilities.